Liturgija v Kopru in v vsej škofiji v 18. stoletju - Likar, Ivan (Acta Histriae, 2001)
Regarding the 18 th century Koper diocese, it can be said that faith was omnipresent at that time in public as well as private life, which is testified by numerous sacral buildings (181), nine monasteries, two convents, about 200 priests (1 per 125 inhabitants), and a number of brotherhoods (only in Koper there were apparently 27 of them). Some kind of landmarks in the religious life of the diocese are synods convened by bishops. In Koper they were held in 1722 (Anton Marija Borromeo), in 1737 (Avguštin de Brutis), in 1766 (Karel Camuccio) and in 1799 (Bonifacij de Ponte) as witnessed by the preserved synodal texts in the diocese's archives. Their contents include accounts of the entire life of the Church, and a special attention is dedicated to the worship of God, which is one of the most pronounced expressions of faithfulness. The instructions are very detailed, from giving sacraments to the worship of St. Nazarij by the open sacrophagues. Very important for the presentation of religious life of a certain time are canonical visitations made by the bishop in his parishes approximately every five years. In the 18th century, thre were no less than 19 of them in the Koper diocese. The stamp of the Koper diocese's faithfulness, especially in rural areas, was through the entire time provided by Glagoliticism. Extremely important for the religious life in the rural areas was the koper Illyric theological seminary (1710-1818). A great event in the 18th century (particularly for Koper) was the enlargement of the cathedral during 1716-1745.
Keywords: 18.st.; bogoslužje; glagoljaši; Koper; liturgy; sinode; škofije